2010
DOI: 10.1002/jez.619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climatic variables on seasonal morphological changes in the testis and epididymis in the wild rodent Microcavia australis from the andes mountains, Argentina

Abstract: It has been shown that seasonal changes, especially in arid areas have a large influence on gonadal changes of the species that inhabit these areas. We studied a wild hystricomorph Microcavia australis in its natural habitat in the arid Andes Mountains. Sampling of adult males was carried out every 2 months. After autopsy, testes and epididymides were weighed and processed to obtain histological samples. Testes were analyzed with a microscope to measure seminiferous tubule area and diameter for each sampled mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…This is an efficient strategy to ensure energy metabolism and successful breeding as an adaptation to the annually changing conditions in their habitat [27]. Meanwhile, these findings were also similar to the observations in roe deer [23], viscacha [25,28] and mountain cavy [24]. In roe deer, the epididymal duct with its surrounding tissue expanded as the breading season approached.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…This is an efficient strategy to ensure energy metabolism and successful breeding as an adaptation to the annually changing conditions in their habitat [27]. Meanwhile, these findings were also similar to the observations in roe deer [23], viscacha [25,28] and mountain cavy [24]. In roe deer, the epididymal duct with its surrounding tissue expanded as the breading season approached.…”
supporting
confidence: 77%
“…These findings suggested that seasonal changes in epididymal morphology and histology were closely associated with the immunoreactivity of the PDGF system in wild ground squirrels. In seasonal breeders, the morphology and function of the epididymis change is synchronized with testicular tissue and spermatogenesis [23][24][25][26]. The present study revealed that similar to the testis [21,22], epididymal morphology also showed a significant seasonal change throughout the year.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In addition, the length of the seminiferous tubule decreased sharply only between MR and SR groups. In animals in which tubular sections have been observed in spermatocyte arrest, as in Syrian hamster, only parameters such as tubular thickness (Simeunovic et al, 2000) or variations in the epithelial, tubular, and interstitial areas (Velez et al, 2010) have been studied, although semiquantitatively. All this also applies to mammals and birds in which epithelial atrophy is stronger (Pelletier, 1986;Madekurozwa et al, 2002;Sch€ on et al, 2004;Blottner et al, 2006;Islam et al, 2010;Ara ujo et al, 2013;Luaces et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the testis is strongly affected by environmental changes (Auvigne et al 2010;Velez et al 2010;Wagener et al 2010;Aurich 2011;Fatet et al 2011). Thus, there are species whose non-breeding season is determined by a decrease in daylight hours, the so-called seasonal breeding animals of short photoperiod (Kr ol et al 2005;Sato et al 2005;Klonisch et al 2006;Islam et al 2009).…”
Section: Introductionmentioning
confidence: 99%